PENERAPAN MODEL GD UNTUK MENINGKATKAN HASIL BELAJAR DAN KETERAMPILAN PROSES SAINS PADA MATERI GHS - Pebrian, Dhea Debra; Djudin, Tomo; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aims to determine the effect of guided discovery learning models to improve learning outcomes and science process skills students? on simple harmonic motion topic in class XI MIA 1 Pontianak. The form of this study is experimental research and the method is one group pre-test post-test design. This study was involved by 30 students from XI MIA 1 with the intact group technique. The instruments of this study are learning outcomes tests that consist of 10 multiple choices and 2 essays, and observation sheet of science process skills which have 4 aspects (observing, hypothesizing, interpreting observations, and communicating). Science process skills students? score in first meeting was 82% (good category), and in the second meeting was 88,25% (excellent category). The results of the analysis of pre-test post-test learning outcomes, and science process skills showed an increase of 4,33% and 6,25% with contribution of learning outcomes to science process skills by 34,69%. This results of study are expected to be an alternative in efforts to improve learning outcomes and science process skills of students on simple harmonic motion material in the application of guided discovery models. Keywords: Guided Discovery, Learning Outcomes, Science Process Skills, Simple Harmonic Motion